PENGARUH PROMOSI TERHADAP PENINGKATAN PENJUALAN - Iskandar, Rhoma; Suarsih, Euis (Pusat Riset dan Inovasi Nasional, 2022)
Promotion is one of the most important marketing mix variables applied by companies in marketing their products. Without promotion, the product gets less attention from consumers. The promotion target can be achieved if the company allocates adequate promotional costs and with the promotion costs it is expected to help the company achieve higher sales volume. This study aims to determine the effect of promotional costs on sales volume. The samples taken in this study were obtained from the financial statements of PT. Gudang Garam Tbk, PT Hanjaya Mandala Sampoerna Tbk and PT Wismilak Inti Makmur Tbk. This study uses a simple linear regression analysis method, testing with a significance of 5%. The results of hypothesis testing, namely the relationship between advertising costs and sales, show that promotional costs have a significant positive effect on sales (significance value 0.000 <0.05). Thus, the hypothesis is supported. The adjusted R Square value is 0.932 or 93.2%, this implies that the regression model has an effect on sales of 93.2% and the rest are other factors that are not measured in this study.